2020
DOI: 10.1021/acsomega.0c01109
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Data Integration Questions Classic Study on Protease Self-Digest Kinetics

Abstract: We combine Bayesian data integration with kinetic modeling to rigorously identify reaction mechanisms. This approach forces models to be consistent not only with kinetic measurements but with all available information. We revisit a classic study on trypsin self-digest acceleration by colloidal silica. Bayesian data integration reveals that the mechanism suggested in that study is inconsistent with its presented data. We propose an improved hypothesis. However, the detailed mechanism of the surface reaction can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This result demonstrated how our approach can be used to generate mechanistic hypotheses explaining complex protein signaling networks. Similar studies concluded after proposing hypotheses (Hug et al, 2013; Tötsch and Hoffmann, 2020). In this work, we moved beyond hypothesis formation by testing the proposed SOCS dynamics.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…This result demonstrated how our approach can be used to generate mechanistic hypotheses explaining complex protein signaling networks. Similar studies concluded after proposing hypotheses (Hug et al, 2013; Tötsch and Hoffmann, 2020). In this work, we moved beyond hypothesis formation by testing the proposed SOCS dynamics.…”
Section: Resultssupporting
confidence: 83%
“…We introduced KL divergence-based clustering, an approach that facilitates hypothesis generation by prioritizing parameters for qualitative analysis. While other approaches for hypothesis formation using posteriors exist, they are largely qualitative and can be time consuming, as they typically require qualitative evaluation of every model parameter (Hug et al, 2013; Thijssen et al, 2018; Tötsch and Hoffmann, 2020). Our approach streamlines the qualitative evaluation of model parameters by using clustering to select only a subset of parameters for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations